Yesus Satu-Satunya Pemberi Kemerdekaan Bagi Orang Berdosa - Fenius Gulo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
This study is aimed to analyze John 8:36 regarding the meaning of the phrase